AKT hyperactivation confers a Th1 phenotype in thymic Treg cells deficient in TGF‐β receptor II signaling. Issue 2 (2nd December 2013) - Liu, Yun; Xu, Yingqian; Sun, Jiabin; Ma, Aihui; Zhang, Feng; Xia, Suhua; Xu, Guiqin; Liu, Yongzhong
<x xml:space="preserve">Abstract</x> The generation of CD4+Foxp3+ Treg cells in the thymus is crucial for immune homeostasis and self‐tolerance. Recent studies have shown Treg‐cell plasticity when Th‐related transcriptional factors and cytokines are present. However, the mechanisms that maintain the stability of Treg cells are poorly understood. Here, using mice with a T‐cell‐specific deletion of the transforming growth factor‐β receptor 2 (Tgfbr2−/− mice), we identify the restriction of AKT activation as a key event for the control of Treg‐cell stability in Th1 inflammation. AKT regulation was evident in thymic CD4+Foxp3+ Treg cells before they egressed to peripheral tissues. CD4+Foxp3+ thymocytes from mice with the Tgfbr2 deletion expressed high levels of CXCR3 and T‐bet, and produced IFN‐γ and TNF‐α. Thymic Tgfbr2−/− Treg cells also showed an increase in the activation of AKT pathway. Enhanced AKT activity induced the expression of IFN‐γ both in natural and inducible Treg cells. Inhibition of AKT activity markedly attenuated the expression of IFN‐γ and TNF‐α in thymic Tgfbr2−/− Treg cells in vivo. In addition, mixed bone marrow transplantation showed that TGF‐β signaling maintained Treg‐cell stability in an intrinsic manner. Our results demonstrate that AKT hyperactivation contributes to the conversion of Treg cells to a Th1 phenotype.